Speciation in Thaparocleidus (Monogenea: Dactylogyridae) parasitizing Asian Pangasiid catfishes - Simková, Andrea; Serbielle, Celine; Pariselle, Antoine; Vanhove, Maarten P M; Morand, Serge (BioMed research international, 2013)
The phylogeny of monogeneans of the genus Thaparocleidus that parasitize the gills of Pangasiidae in Borneo and Sumatra was inferred from molecular data to investigate parasite speciation. The phylogeny of the Pangasiidae was also reconstructed in order to investigate host-parasite coevolutionary history. The monophyly of Thaparocleidus parasitizing Pangasiidae was confirmed. Low intraspecies molecular variability was observed in three Thaparocleidus species collected from geographically distant localities. However, a high intraspecies molecular variability was observed in two Thaparocleidus species suggesting that these species represent a complex of species highly similar in morphology. Distance-based and tree-based methods revealed a significant global fit between parasite and host phylogenies. Parasite duplication (i.e., intrahost speciation) was recognized as the most common event in Thaparocleidus, while the numbers of cospeciation and host switches were lower and similar to each other. When collapsing nodes correspond to duplication cases, our results suggest host switches in the Thaparocleidus-Pangasiidae system precluding congruence between host and parasite trees. We found that the morphometric variability of the parasite attachment organ is not linked to phylogeny, suggesting that the attachment organ is under adaptive constraint. We showed that haptor morphometry is linked to host specificity, whereby nonspecific parasites display higher morphometric variability than specialists.
Keywords: Catfishes; Phylogeny; druhová specificita; Gills; fylogeneze; Animals; lidé; Asian People; Species Specificity; sumci; žábry; Asijci; Host-Parasite Interactions; Humans; zvířata; interakce hostitele a parazita